Atacicept in patients with rheumatoid arthritis and an inadequate response to methotrexate: Results of a phase II, randomized, placebo‐controlled trial - van Vollenhoven, R. F.; Kinnman, N.; Vincent, E.; Wax, S.; Bathon, J. (Arthritis & rheumatology (Hoboken, N.J.), 2011)
Objective To assess the efficacy, safety, and biologic activity of atacicept in tumor necrosis factor antagonist–naive patients with rheumatoid arthritis (RA) in whom the response to methotrexate treatment was inadequate. Methods In this phase II study, patients with active RA (n = 311) were randomized 1:1:1:1 to receive placebo, atacicept 150 mg weekly with or without a 4‐week loading period (twice‐weekly dosing), or open‐label adalimumab 40 mg every other week, for 25 weeks. The primary end point was 20% improvement in disease severity according to the American College of Rheumatology criteria, assessed using the C‐reactive protein level (ACR20‐CRP), at week 26. Secondary end points included additional assessments of efficacy, biologic activity, and safety. Results The proportion of patients meeting the primary end point (ACR20‐CRP response) did not differ significantly in the atacicept groups and the placebo group (46% in the placebo group, 45% in the atacicept loading group, and 58% in the atacicept nonloading group). In contrast, an ACR20‐CRP response was observed in 71% of patients in the adalimumab group (P < 0.001 versus placebo). ACR50‐CRP response rates were significantly higher in all active‐treatment groups compared with placebo, but ACR70‐CRP response rates were superior only in the adalimumab group. Atacicept treatment reduced the levels of serum IgG, IgA, and IgM rheumatoid factor and the levels of circulating mature B cells and plasma cells. The effects of treatment were similar with and without loading. Immunoglobulin levels returned toward baseline values during the treatment‐free followup period (week 38). The most frequent adverse events associated with atacicept represented common illnesses. No serious infections occurred among patients treated with atacicept. Conclusion The primary end point (ACR20‐CRP response) was not met despite significant biologic effects of atacicept that were consistent with its proposed mechanism of action. Modest effects of atacicept were seen for some secondary efficacy end points. Treatment with atacicept raised no new safety concerns.